Sakramentarze źródłami kolekt w Mszale rzymskim Pawła VI - Kreczmański, Sebastian (Studia Pastoralne, 2026)
At every Eucharist the Church explains the revealed truths to the confessors. For this purpose it uses the ministers of the sacred mysteries. The content that is explained is, primarily, the true Word of God, because this is what constitutes one of the main sources of the Church doctrine. The second source is the Tradition. We owe liturgical prayers to it. Their present form is very different from the one which they had during the time of creation. The extraordinary cultural enrichment of the Church is based on activities aimed at reaching the sources from which there were derived the prayers used during the celebration. These actions aim to acquire knowledge of various ways of celebrating the same mystery that Christ commanded to celebrate to the whole Church. Through the knowledge of the sources, the believers in Christ can reach deeper into the jewel of the gifts of the Holy Spirit who is always present in the Church. Thematically the opening prayers bring the image of God, which is confessed by the Church and transmitted by means of the multi-century tradition as its greatest treasure, closer to the confessors. The purpose of the liturgical prayers of the Church is not just a verbal confession of faith, but also its verification in life that is identified with the existentially understood faith. Therefore it appears to be necessary for the faithful to know the history of the liturgical prayer, so that it can better contribute to the daily attitude of Christians.